THE ROLE OF THE SOCIAL ENVIRONMENT IN THE DEVELOPMENT OF YOUTH CULTURE (Multidisciplinary Journal of Science and Technology, 2024)
This article provides an opinion on the education of youth and its current problems in modern rapidly developing times, using wise sayings and lessons of great scientists and thinkers. The article also discusses the views of Eastern scientists on the process of education.